The equation of a line is the form of
[tex]\begin{gathered} y\text{ = mx +c} \\ \text{where} \\ m\text{ = slope} \\ \text{and} \\ c\text{ = y-intercept} \end{gathered}[/tex]The equation of the line was, however, given as
[tex]5x-3y\text{ = (-9)}[/tex]To rewrite this equation in slope-intercept form, we must first find the slope and y-intercept from the equation by rearranging it
[tex]\begin{gathered} 5x+9=3y \\ 3y\text{ = 5x+9} \\ \frac{3y}{3\text{ }}=\frac{5x}{3}+\frac{9}{3} \\ y\text{ = }\frac{5}{3}x+3 \\ \text{From here the slope, m =}\frac{5}{3} \\ \text{and } \\ \text{the y-intercept, c = 3} \end{gathered}[/tex]Hence the required equation is y =(5/3)x +3. The answer is the third option